Official use of minority languages: between symbolic politics and local public policies - Wołek Artur; Wądołowski Marcin („RIK-U” Kft., 2018)
Abstract. The official use of minority languages is studied mostly in terms of its symbolic function for minorities empowerment. It is widely accepted that the recognition of the minority language as a means of communication between authorities and population as well as officially recognized and displayed geographical names are crucial for the self-perception of minorities as equal citizens. The official use of minority languages creates also territorially delimited “semantic landscape” or “symbolic domain” where minorities feel at home and can freely cultivate their identities [Alderman 2008; 195–204; Jaworski and Thurlow 2010; Marten 2012]. Very rarely however practical consequences of the official use of minority languages are studied. How does the dual official language function in local authorities daily routine? Is the dual official language status used as a resource for development strategies of local communities? Is it used as an instrument for building a distinctive image of the local community? These questions are posed only occasionally and theoretical tools supplied by the public policy analysis are hardly ever applied to the study of the official use of minority languages. The above questions applied to the Polish circumstances guided a research project the results of which are presented in this paper.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: minority languages; local public policy; Poland